TOURISM ON THE AZORES AND MADEIRA ISLANDS: ISSUES OF PERIPHERAL AND DEVELOPMENT REGIONS - Sandra Dias Faria; Maria Teresa Borges Tiago; Flávio Gomes Borges Tiago; João Pedro Couto (European Scientific Journal, ESJ, 2014)
In general all governments, be they local or national, have a policy for tourism, whether it represents an active involvement or a laissez-faire approach. This strategic approach reflects in different areas concerning the support for human resource development and practices in tourism. As result of this human resource strategy the determinants factors of how employees fit a particular job ina particular organization at a particular location will vary. Regardless the relevance of this topic, few research works have been carry out in this domain. Therefore, in this paper, we briefly address the nature of tourism as a sector within the economy and identify the determinants of the human resources strategy evolution in terms of the key themes in this paper. Since the role of human resources in enabling tourism businesses is critical, this work discusses the theoretical implications andapplications for meeting workforce challenges of tourism organizations, associations and destinations, especially those in remotelocations.